TGF-β-induced autophagy in pulmonary artery endothelial cells associated with chronic thromboembolic pulmonary hypertension - Ying-Ju Lai; Yen-Lin Huang; Ching-Yen Tsai; Po-Ru Chen; Chi-Jen Chang; Yung-Hsin Yeh; Celina De Almeida; Hsao-Hsun Hsu (Journal of Molecular Medicine, 2026)

Pyridoxine and valproic acid co-exposure induces ER-mediated calcium dysregulation and cardiac toxicity in zebrafish - Wei-Hsiang Chen; Po-Yuan Chen; Wen-Yu Chung; Tein-Yu Chiu; Wei-Ling Lin; Chen-Yu Huang; Hui-Hua Chang; Chin-Wei Huang; Bing-Hung Chen; Lin Kang; Tzu-Fun Fu (Chemico-Biological Interactions, 2026)

Laser dewetting-induced metal particles and their antimicrobial effects - H.K. Lin; Min-Yang Chen; Po-Wei Chang; Ya-Zhen Xu; Ying-Hong Lin (Physiological and Molecular Plant Pathology, 2026)

Phylogeny and taxonomic revisions of Piper (Piperaceae) in Taiwan - Po-Hao Chen; Chia-Hao Chang; Kuan-Ning Kung; Hung‑Chih Lin; An-Ching Chung; Chia-Ying Ou; Shih-Hui Liu (Journal of Plant Research, 2026)
Taiwan, located at the northernmost extent of Huxley’s Line, marks the furthest point along this biogeographic boundary where exchanges of flora and fauna occur. The genus Piper , a globally distributed and taxonomically complex group of both economic and evolutionary importance, has a convoluted taxonomic history in this transitional zone that requires comprehensive study. Here, we integrate morphological, molecular, and distributional data to revise the taxonomy of Taiwanese Piper , resolve their evolutionary relationships, and infer their biogeographic history. Our revision recognizes 11 species in Taiwan, including seven native taxa, of which three are endemic. The present analysis establishes the first comprehensive phylogenetic framework for Taiwanese Piper and reveals that native species arose from lineages on both sides of Wallace’s Line. Collectively, these findings provide the first evidence of bidirectional expansion within a genus in Taiwan and position Piper as an exemplary system for examining phylogeographic dynamics in transitional biogeographic zones.

Plant–soil feedback persists beyond host death to shape density-dependent plant competition - Ching-Lin Huang; Joe Wan; Shuo Wei; Chia-Hao Chang-Yang; Po-Ju Ke (Plant and Soil, 2026)

Pollutant-specific pathways linking gaseous air pollution to adolescent depressive symptoms: Direct and sleep-mediated effects in a population-based retrospective cohort study - Chun-Ji Lin; Po-Ya Chang; Yu-Ling Li; Chih-Da Wu; Chao-Ying Tu; Chih-Yi Wu; Szu-Ying Chen; Hung-Yi Chiou (Environmental Research, 2026)

Comparative Online–offline measurement of airborne toxic VOCs for health risk and source identification in an environmental justice community - Hsin-Cheng Hsieh; Yuan-Chang Su; Sheng-Po Chen; Chen-Hsuan Chu; Mei-Hui Tseng; Kuan-Chun Lee; Po-Sheng Tseng; Pei-Hsuan Hsu; Chih-Chung Chang; Chieh-Heng Wang; Jia-Lin Wang (Atmospheric Environment, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Thiourea-based networks with nanocarbon fillers for antistatic, self-healing, and plasma-resistant elastomers - Tse-Yu Lo; Shu-Fan Li; Chia-Wei Chang; Huan-Wei Lin; Heng-Hsuan Su; Kuan-Hung Liu; Po-Chia Huang; Jiun-Tai Chen (Chemical Engineering Journal, 2026)

Association between urinary metabolites of 1,3-butadiene and toluene exposure with kidney function indices in Taiwanese school-aged children living near a petrochemical complex - Po-Keng Cheng; Vinoth Kumar Ponnusamy; Wei-Hong Lin; Jeganathan Chinnadurai; Pei-Chien Tsai; Cai-Yu Chen; Wan-Ting Chang; Po-Chin Huang (Environmental Pollution, 2026)

Harnessing pyroptosis to restrain melanoma through aripiprazole - Yu-Teng Chang; I-Hsiang Lin; Jeng-Jer Shieh; Tsuo-Hung Lan; Jia-Ning Syu; Shiau-Shian Huang; Po-Hsun Hou (Apoptosis, 2026)

Microfluidic device for high-throughput cancer drug screenings - Po-Hsun Chen; Lin-Yu Wang; Chia-Yuan Chang; Yuh-Shiuan Chien; Yu-Chia Su; Chi-Kuang Wang; Kuang-Chong Wu; Hsian-Jean Chin; Chien-Fu Chen (Chemical Engineering Journal, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Comparing tea-drinking experiences in virtual outdoor landscape restaurants with different levels of perceived environmental naturalness - Pei-Lun Sun; Yeqiang Kevin Lin; Po-Ju Chang (Landscape and Ecological Engineering, 2025)

Establishment of a pseudotargeted LC‒MS/MS workflow for analyzing triglycerides in biological samples - Wei-Chieh Wang; Chin-Yi Wang; Ta-Chen Su; Po-Chih Lin; Wen-Chi Chang; Kuei-Pin Chung; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

Synergistic properties of single-component hexagonal iron borate for superior and sustainable photo-Fenton catalysis - Po-Yi Wu; Jing-Cheng Hsu; Tsung-Yueh Lin; Yu-Lun Zhu; Yu-Rong Chang; Pei Yuin Keng (Journal of Environmental Chemical Engineering, 2025)

Exploring the causal relationships between environmental factors and benthos distributions in an intertidal algal reef ecosystem via a structural equation model - Chun-Wei Wu; Shih-wei Liao; Showe-Mei Lin; Shou-Chung Huang; Chang-Po Chen; Po-Kang Shih; Hwey-Lian Hsieh (Continental Shelf Research, 2025)

Leveraging Bio-Waste onion skin for High-Performance triboelectric nanogenerators - Po-Yen Chang; Ting-Ying Huang; Chien-Hung Yang; Chia-Hsien Lee; Ru-Jong Jeng; Chih-Ping Chen; Meng-Fang Lin (Chemical Engineering Journal, 2025)

Homogeneous crystallization of nickel as Ni₃S₄ in a fluidized bed reactor with supersaturation control - Po-Lin Liao; Laurencia Wiryana Effendi; Nicolaus Nezha Nunez Mahasti; Kai-Yang Chang; Yao-Hui Huang (Journal of Environmental Chemical Engineering, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Is an invasive species a notorious invader or carbon sequencer? - Karlia Meitha; Po-Yi Chen; Chieh Chang; Zi-Ci Lin; Tsai-Wen Hsu; Takashi Gojobori; Tzen-Yuh Chiang (Ecological Genetics and Genomics, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Enhanced precipitation of CaMoO4 for continuous recovery of molybdenum from Mo-contained wastewater and application to fluidized bed homogeneous crystallization - Jing-Hao Lin; Kai-Yang Chang; Po-Lin Liao; Yao-Hui Huang (Journal of Water Process Engineering, 2024)

3D Effect and countermeasure of 2D geoelectrical imaging of a subsurface linear structure - Yin-Chun Hung; Haoran Wang; Po-Lin Wu; Hsin-Chang Liu; Chih-Ping Lin (Engineering Geology, 2024)

Unlocking the ocean's potential: enhancing carbon capture through innovative replacement of methane hydrate by CO2 - Ting-Ting Chang; Wonjung Choi; Yongwon Seo; Anisa Fitri Santosa; Jian-Jhih Lin; Po-Yu Chen; Yao-Chuan Tasi; Wu-Yang Sean (Modeling Earth Systems and Environment, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

The Bioeconomic Analysis of Hybrid Giant Grouper (Epinephelus fuscoguttatus × Epinephelus lanceolatus) and Green Grouper (Epinephelus malabaricus): A Case Study in Taiwan - Po-Lin Huang; Farok Afero; Yao Chang; Bo-Ying Chen; Hsun-Yu Lan; Yen-Lung Hou; Cheng-Ting Huang (Fishes, 2023)
Grouper aquaculture is a rapidly growing and dynamic industry within the Taiwan aquaculture sector that serves as an important source of income generation. Farming fishes at a better location (FFABL) is a promising production strategy. This study evaluated the production and economic performance of grouper farming in Taiwan. This investigation employed two steps: (1) a cost–benefit analysis to determine the main component affecting profitability; and (2) multivariate statistics to clarify the relationship between biological and economic factors. The findings suggest that the best choice of species is hybrid giant grouper that generates and highlights a positive income, viable benefit–cost ratio and profit rate. The study found the feed management of hybrid giant groupers requires more consideration due to its low feed conversion ratio. The producers need to replace trash fish in commercial feed during the production cycle to ensure better feed management. Finally, this paper argues that feed is the main constraint for grouper farming, which is sensitive to any change in feed productivity, and this constraint must be solved to sustain the grouper industry in Taiwan.

Inhibition of continuous cropping obstacle of celery by chemically modified biochar: An efficient approach to decrease bioavailability of phenolic allelochemicals - Chia-Chia Lin; Yu-Ting Liu; Po-Hsiang Chang; Yi-Cheng Hsieh; Yu-Min Tzou (Journal of Environmental Management, 2023)

Associations between paraben exposure, thyroid capacity, homeostasis and pituitary thyrotropic function in the general Taiwanese: Taiwan Environmental Survey for Toxicants (TEST) 2013 - Po-Chin Huang; Hsin-Chang Chen; Shih-Hao Leung; Yu-Jung Lin; Han-Bin Huang; Wan-Ting Chang; Hsin-I. Huang; Jung-Wei Chang (Environmental Science and Pollution Research, 2023)

Quantifying the potential effects of air pollution reduction on population health and health expenditure in Taiwan - Yi-Hsuan Roger Chen; Wan-Chen Lee; Bo-Chen Liu; Po-Chieh Yang; Chi-Chang Ho; Jing-Shiang Hwang; Tzu-Hsuan Huang; Hsien-Ho Lin; Wei-Cheng Lo (Environmental Pollution, 2023)

Nanoscale photocatalytic hydrogen production system mitigates inflammation by harnessing glycolysis waste - Cheng-Yu Wu; Cam-Hoa Mac; Tung-Han Yang; Khanh Nguyen; Shih-Kai Lo; Yen Chang; Po-Liang Lai; Hsing-Wen Sung; Yu-Jung Lin (Chemical Engineering Journal, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

Magnusiomyces Capitatus Lung Nodule in a Patient with Nasopharyngeal and Hepatocellular Carcinoma - Shih-Hao Lo; Hsin-Hui Wang; Ya-Ting Chang; Chih-Hung Lin; Po-Liang Lu; Shang-Yi Lin (Mycopathologia, 2023)

High carriage rate of extended‐spectrum β‐lactamase Enterobacterales and diarrheagenic Escherichia coli in healthy donor screening for fecal microbiota transplantation - Chien Chuang; Kuei-Chuan Lee; Yen-Po Wang; Pei-Chang Lee; Tien-En Chang; Yi-Hsiang Huang; Yi-Tsung Lin; Ming-Chih Hou (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Antiherbivore effect of Cuscuta campestris against Spodoptera frugiperda - Chang-Lin Sung; Fang-Yu Hu; Yi Li; Shin-Fu Tsai; Wen-Po Chuang (Arthropod-Plant Interactions, 2023)

Infusing satellite data into aerosol forecast for near real-time episode detection and diagnosis in East Asia - Sheng-Po Chen; Cheng-Hsuan (Sarah) Lu; James E. Davies; Chang-Feng Ou-Yang; Neng-Huei Lin; Amy K. Huff; Bradley R. Pierce; Shobha Kondragunta; Jia-Lin Wang (Science of The Total Environment, 2023)

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

Structure related α-glucosidase inhibitory activity and molecular docking analyses of phenolic compounds from Paeonia suffruticosa - Po-Chun Chen; Bongani Sicelo Dlamini; Chiy-Rong Chen; Yueh-Hsiung Kuo; Wen-Ling Shih; Yun-Sheng Lin; Chien-Hsing Lee; Chi-I Chang (Medicinal Chemistry Research, 2022)

Electrical Impedance Tomography Analysis Between Two Similar Respiratory System Compliance During Decremetal PEEP Titration in ARDS Patients - Po-Lan Su; Wei-Chieh Lin; Yen-Fen Ko; Kuo-Sung Cheng; Chang-Wen Chen (Journal of Medical and Biological Engineering, 2021)
Purpose The positive end-expiratory pressure (PEEP) level with best respiratory system compliance (Crs) is frequently used for PEEP selection in acute respiratory distress syndrome (ARDS) patients. On occasion, two similar best Crs (where the difference between the Crs of two PEEP levels is < 1 ml/cm H 2 O) may be identified during decremental PEEP titration. Selecting PEEP under such conditions is challenging. The aim of this study was to provide supplementary rationale for PEEP selection by assessing the global and regional ventilation distributions between two PEEP levels in this situation. Methods Eight ARDS cases with similar best Crs at two different PEEP levels were analyzed using examination-specific electrical impedance tomography (EIT) measures and airway stress index (SIaw). Five Crs were measured at PEEP values of 25 cm H 2 O (PEEP 25 ), 20 cm H 2 O (PEEP 20 ), 15 cm H 2 O (PEEP H ), 11 cm H 2 O (PEEP I ), and 7 cm H 2 O (PEEP L ). The higher PEEP value of the two PEEPs with similar best Crs was designated as PEEP upper , while the lower designated as PEEP lower . Results PEEP H and PEEP I shared the best Crs in two cases, while similar Crs was found at PEEP I and PEEP L in the remaining six cases. SIaw was higher with PEEP upper as compared to PEEP lower (1.06 ± 0.10 versus 0.99 ± 0.09, p = 0.05). Proportion of lung hyperdistension was significantly higher with PEEP upper than PEEP lower (7.0 ± 5.1% versus 0.3 ± 0.5%, p = 0.0002). In contrast, proportion of recruitable lung collapse was higher with PEEP lower than PEEP upper (18.6 ± 4.4% versus 5.9 ± 3.7%, p < 0.0001). Cyclic alveolar collapse and reopening during tidal breathing was higher at PEEP lower than PEEP upper (34.4 ± 19.3% versus 16.0 ± 9.1%, p = 0.046). The intratidal gas distribution (ITV) index was also significantly higher at PEEP lower than PEEP upper (2.6 ± 1.3 versus 1.8 ± 0.7, p = 0.042). Conclusions PEEP upper is a rational selection in ARDS cases with two similar best Crs. EIT provides additional information for the selection of PEEP in such circumstances.

Recycle of synthetic calcium fluoride and waste sulfuric acid to produce electronic grade hydrofluoric acid - Min-Fa Lin; Jhong-Lin Wu; Ken-Lin Chang; Wen-Jhy Lee; Chih-Ping Chang; Yung-Chang Lin; Po-Han Chen (Environmental Science and Pollution Research, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Infusion of Human Mesenchymal Stem Cells Improves Regenerative Niche in Thioacetamide-Injured Mouse Liver - Ying-Hsien Kao; Yu-Chun Lin; Po-Huang Lee; Chia-Wei Lin; Po-Han Chen; Tzong-Shyuan Tai; Yo-Chen Chang; Ming-Huei Chou; Chih-Yang Chang; Cheuk-Kwan Sun (Tissue Engineering and Regenerative Medicine, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Prior Antiplatelet Therapy, Excluding Phosphodiesterase Inhibitor Is Associated with Poor Outcome in Patients with Spontaneous Intracerebral Haemorrhage - Zhuo-Hao Liu; Chi-Hung Liu; Po-Hsun Tu; Ping K. Yip; Ching-Chang Chen; Yu-Chi Wang; Nan-Yu Chen; Yu-Sheng Lin (Translational Stroke Research, 2020)

The potential of satellite remote sensing for monitoring the onset of volcanic activity on Taipei’s doorstep - Hai-Po Chan; Chung-Pai Chang; Tang-Huang Lin; Matthew Blackett; Hao Kuo-Chen; Andrew Tien-Shun Lin (International Journal of Remote Sensing, 2020)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

Characterization and adsorption capacity of potassium permanganate used to modify activated carbon filter media for indoor formaldehyde removal - Shih-Cheng Hu; Ying-Chen Chen; Xin-Zhi Lin; Angus Shiue; Po-Hua Huang; Yen-Che Chen; Shu-Mei Chang; Chao-Heng Tseng; Bin Zhou (Environmental Science and Pollution Research, 2018)

Expression of serine peptidase inhibitor Kunitz type 1 in differentiated thyroid cancer - Chien-Liang Liu; Po-Sheng Yang; Ming-Nan Chien; Yuan-Ching Chang; Chi-Hsin Lin; Shih-Ping Cheng (Histochemistry and Cell Biology, 2018)

Treatment outcome of non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae infections: a multicenter study in Taiwan - Chin-Fang Su; Chien Chuang; Yi-Tsung Lin; Yu-Jiun Chan; Jung-Chung Lin; Po-Liang Lu; Ching-Tai Huang; Jann-Tay Wang; Yin-Ching Chuang; L. Kristopher Siu; Chang-Phone Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Hydrology Drives Vegetation Succession in a Tidal Freshwater Wetland of Subtropical Taiwan - Hsing-Juh Lin; Chun-Han Huang; Gwo-Wen Hwang; Chorng-Bin Hsu; Chang-Po Chen; Hwey-Lian Hsieh (Wetlands, 2016)

Hybrid Electrospun Polycaprolactone Mats Consisting of Nanofibers and Microbeads for Extended Release of Dexamethasone - Kuan-Hui Hsu; Sheng-Po Fang; Chang-Lin Lin; Yan-Shin Liao; Yong-Kyu Yoon; Anuj Chauhan (Pharmaceutical Research, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Sulbactam treatment for pneumonia involving multidrug-resistant Acinetobacter calcoaceticus–Acinetobacter baumannii complex - Huang-Shen Lin; Ming-Hsun Lee; Chun-Wen Cheng; Po-Chang Hsu; Hsieh-Shong Leu; Ching-Tai Huang; Jung-Jr Ye (Infectious Diseases, 2015)

Effects of Spartina alterniflora Invasion on the Abundance and Community of Meiofauna in a Subtropical Wetland - Hsing-Juh Lin; Chorng-Bin Hsu; Szu-Han Liao; Chang-Po Chen; Hwey-Lian Hsieh (Wetlands, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Classification of Benign and Malignant Breast Tumors in Ultrasound Images with Posterior Acoustic Shadowing Using Half-Contour Features - Zhuhuang Zhou; Shuicai Wu; King-Jen Chang; Wei-Ren Chen; Yung-Sheng Chen; Wen-Hung Kuo; Chung-Chih Lin; Po-Hsiang Tsui (Journal of Medical and Biological Engineering, 2015)

Genetic diversity and identification of race 3 of Fusarium oxysporum f. sp. lactucae in Taiwan - Ying-Hong Lin; Po-Jung Lai; Tao-Ho Chang; Yu-Ling Wan; Jenn-Wen Huang; Jin-Hsing Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2014)

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan - Mao-Wang Ho; Yun-Liang Yang; Chih-Chao Lin; Chih-Yu Chi; Hui-Ting Chen; Po-Chang Lin; Li-Yun Hsieh; Chia-Hui Chou; Wen-Li Chu; Chiou-Pyng Wu; Tsai-Ling Lauderdale; Hsiu-Jung Lo (Mycopathologia, 2014)

Gemifloxacin inhibits migration and invasion and induces mesenchymal–epithelial transition in human breast adenocarcinoma cells - Tun-Chieh Chen; Ya-Ling Hsu; Yu-Chieh Tsai; Yu-Wei Chang; Po-Lin Kuo; Yen-Hsu Chen (Journal of Molecular Medicine, 2014)

Telbivudine and adefovir combination therapy for patients with chronic lamivudine-resistant hepatitis B virus infections - Ming-Tsung Lin; Yeh-Pin Chou; Tsung-Hui Hu; Hsien-Chung Yu; Yu-Chun Hsu; Ming-Chao Tsai; Po-Lin Tseng; Kuo-Chin Chang; Yi-Hao Yen; King-Wah Chiu (Archives of Virology, 2014)

Chromium levels in insulin-sensitive tissues and the thigh bone are modulated by prednisolone and high-fat diets in mice - Po-Wen Chen; Chang Lin; Chung-De Chen; Wen-Ying Chen; Frank Chiahung Mao (BioMetals, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Comparison of MODIS land surface temperature and ground-based observed air temperature in complex topography - Yen-Jen Lai; Ching-Feng Li; Po-Hsiung Lin; Tsong-Hue Wey; Cheng-Sheng Chang (International Journal of Remote Sensing, 2012)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Effect of Sulfate Availability on the Isotopic Signature of Reduced Sulfurous Compounds in the Sediments of a Subtropical Estuary - Lan-Feng Fan; Saulwood Lin; Wei-Gang He; Kuo-Ming Huang; Chang-Po Chen; Hwey-Lian Hsieh (Wetlands, 2012)

Oxidative stress in greater duckweed (Spirodela polyrhiza) caused by long-term NaCl exposure - In-Hwa Chang; Kai-Teng Cheng; Po-Chuan Huang; Yen-Yu Lin; Lee-Ju Cheng; Tai-Sheng Cheng (Acta Physiologiae Plantarum, 2012)

Evaluation of the optimal strategy for ex situ bioremediation of diesel oil-contaminated soil - Ta-Chen Lin; Po-Tsen Pan; Chiu-Chung Young; Jo-Shu Chang; Tsung-Chung Chang; Sheng-Shung Cheng (Environmental Science and Pollution Research, 2011)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Prevention of TGF-β-induced apoptosis by interlukin-4 through Akt activation and p70S6K survival signaling pathways - Sue-Jane Lin; Chungming Chang; Ah-Kau Ng; Shu-Han Wang; Jia-Je Li; Cheng-po Hu (Apoptosis, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

A Natural Compound (Ginsenoside Re) Isolated from Panax ginseng as a Novel Angiogenic Agent for Tissue Regeneration - Ya-Chun Huang; Chiung-Tong Chen; Sung-Ching Chen; Po-Hong Lai; Huang-Chien Liang; Yen Chang; Lin-Chien Yu; Hsing-Wen Sung (Pharmaceutical Research, 2005)

Conservation of the horseshoe crab at Kinmen, Taiwan: strategies and practices - Chang-Po Chen; Hsin-Yi Yeh; Po-Fen Lin (Biodiversity and Conservation, 2004)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)